Fibroblast growth factor 10 markedly improves in vitro maturation of porcine cumulus‐oocyte complexes. Issue 1 (13th January 2017) - Son, Yeo‐Jin; Lee, Seung‐Eun; Hyun, Hyuk; Shin, Min‐Young; Park, Yun‐Gwi; Jeong, Sang‐Gi; Kim, Eun‐Young; Park, Se‐Pill
SUMMARY: Growth factors synthesized by ovarian somatic cells affect cumulus cell expansion and oocyte maturation in vitro. Fibroblast growth factor 10 (FGF10), for example, is a known regulator of mammalian cumulus‐oocyte complex maturation. In this study, we investigated the effects of 0, 5, 10, 50, and 100 ng/mL FGF10 (5F, 10F, 50F, and 100F, respectively) on in vitro cumulus cell expansion, oocyte maturation, and embryo development. The percentage of fully expanded cumulus cells at the oocyte's metaphase‐II (MII) stage was significantly higher in the 10F‐treated group than in the control. Transcript abundance of the cumulus cell expansion‐related gene encoding hyaluronian synthase 2 ( HAS2 ) in cumulus cells at oocyte germinal vesicle breakdown (GVBD) was significantly higher in the 10F‐ and 50F‐treated groups compared to untreated controls, whereas the mRNA abundance of the protease cathepsin B ( CTSB ) at the oocyte MII stage was remarkably decreased in the 10F‐treated group. The percentage of oocytes with normal spindles was greater in the 10F‐ and 50F‐treated group at GVBD than in the other groups; the 5F‐, 10F‐, and 100F‐treated groups were higher than the control; and the 50F‐treated group was highest at MII. The abundance of GDF9 and BMP15 transcript at GVBD and BMP15 and CCNB1 transcripts at MII increased in the 10F‐treated group. Cleavage rate, blastocyst formation rate, and total cell number were significantly higher in the 5F‐ to 50F‐treated groups. These results demonstrate that FGF10 markedly improves cumulus cell expansion, oocyte maturation, and subsequent embryo development. Mol. Reprod. Dev. 84: 67–75, 2017. © 2016 Wiley Periodicals, Inc .